2018
DOI: 10.1021/acs.jpcc.8b06974
|View full text |Cite
|
Sign up to set email alerts
|

Lower Limit of Interfacial Thermal Resistance across the Interface between an Imidazolium Ionic Liquid and Solid Surface

Abstract: Understanding of energy transport across the solid–liquid interface is essential for the rational design of efficient heat dissipation capabilities. In this work, we show that the molecular orientation of liquid near the solid surface dominates the thermal transport across the imidazolium ionic liquids (IL)/graphene interface via molecular dynamics simulations. The molecular orientation is defined as the parallelism between the imidazole ring in IL and graphene and is controlled by wettability of graphene. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 52 publications
1
23
0
1
Order By: Relevance
“…To describe the ordering and distribution of ions at the interface, the mean orientation distribution (P) of the imidazole ring and [OTf] À in ILs is calculated as follows [Eq. (1)]: [29]…”
Section: Variation Of Ionic Orientation Induced By the External Electrical Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…To describe the ordering and distribution of ions at the interface, the mean orientation distribution (P) of the imidazole ring and [OTf] À in ILs is calculated as follows [Eq. (1)]: [29]…”
Section: Variation Of Ionic Orientation Induced By the External Electrical Fieldmentioning
confidence: 99%
“…As the distance from metal surface increases, the configuration of imidazole ring and anion will transform from parallel case (d < 4 Å) to vertical case (4 < d < 7 Å), and finally to the random distribution (d > 10 Å), demonstrating the layered structures reported by the previous works. [29] To measure the influence of alkyl chain length and sulfonic group on the average orientation P ave systematically, all the results of P ave for different ILs were summarized in Figure 4. The P ave of ring and anion in bulk C N mimOTf at the different electrical fields are close to 0.0 (Figure 4a-b), meaning that the ILs distributes randomly and the E is smaller than the inner electrical field between cation and anion.…”
Section: Variation Of Ionic Orientation Induced By the External Electrical Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we investigated the reaction mechanism of the cleavage of β-O-4 bond in GG to guaiacol by -SO 3 H functionalized ILs (Zhang et al, 2019). Given the versatility of IL catalysts (He et al, 2015; Wang et al, 2015; Meng et al, 2017; Qian et al, 2018; Zhang et al, 2018) and our keen interest in the research of biomass (Cai et al, 2015; Suresh et al, 2017), an elegant approach for catalytic transform of lignin to structurally defined aromatic esters is put forward here. According to Otera (1993) and Hoydonckx et al (2004), the lignin model compound, phenyl p-hydroxycinnamate ( PPC ), was used to produce MPC by cleavage of the γ-O ester linkage using MBIL [Bmim][FeCl 4 ] as catalyst (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…First, G g/Au was determined to be ~ 50 MW/(m 2 K) using data at f > 10 5 Hz, where the value seems plausible, referring to a previous report 32 . Then, G Au/IL was fixed at 50 MW/(m 2 K) because G Au/IL is presumed to be > 10 MW/(m 2 ·K) 33 , 34 , and we found that the contribution of G Au/IL to the phase lag at f ~ 10 4 –10 5 Hz is negligible when G Au/IL > 10 MW/(m 2 K). Finally, d IL and G LCCO for A were determined to be ~ 700 nm and 4 MW/(m 2 K), respectively, by analytical fitting.…”
Section: Resultsmentioning
confidence: 83%